Gender differences in arousal priming effects on humor advertising. Issue 3 (3rd April 2019) - Yoon, Hye Jin; Lee, Yoon-Joo
Abstract: Numerous studies have observed arousal and mood effects on ad processing, but no study has examined the ways in which the core arousal effect in humor advertising, which could make or break humor advertising effectiveness, could be boosted or hindered. To address this gap, we investigated arousal priming effects and its influence on humor ad responses, using gender as a moderating variable. Two experimental studies tested the interaction between (a) low and high arousal priming effects and (b) gender on consumer responses to a subsequent humor ad. The results show that men and women responded differently to humor ads presented after low vs. high arousal level primes. A moderated mediation analysis revealed that felt arousal during humor ad exposure was an underlying mechanism. Theoretical and practical implications are discussed.